Metabolism of testosterone during weight loss in men with obesity - Van de Velde, Frederique; Deventer, Koen; Van Gansbeke, Wim; Van Eenoo, Peter; Van Renterghem, Pieter; Fiers, Tom; Reyns, Tim; Kaufman, Jean Marc; Van Nieuwenhove, Yves; Lapauw, Bruno (The Journal of steroid biochemistry and molecular biology, 2021)
•Three weeks after bariatric surgery SHBG and testosterone serum levels increase.•Decreased aromatization contributes to restoration of sex steroid profile.•Decreased metabolism of testosterone by the 5alpha-reductase pathway.•Increased production of testosterone is possible after bariatric surgery. Men with obesity often have low total and, with increasing adiposity, also low free testosterone (T) levels, which can partially restore during weight loss. Although this is partly explained by lower sex hormone binding globulin (SHBG) production and hypothalamic-pituitary downregulation, it is still not unravelled whether changes in androgen metabolism contribute to this phenomenon. Therefore, early changes in urinary excretion of T and its metabolites, during weight loss, in men with obesity are investigated. Longitudinal study. Fourteen men with obesity (age 52(45–60)years, BMI 42.6(41.8–44.8)kg/m²) underwent gastric bypass surgery (GBS). Before surgery and 3 weeks, 6 weeks, 6 months and 1 year thereafter, 24 h urine and fasting serum samples were collected. Serum T and estradiol (E2) levels were analyzed using LC-MS/MS and urinary metabolites of T with GC-MS/MS. Already three weeks after GBS, serum SHBG and total T levels increased and remained increased as compared to baseline (all,p < 0.0125). Gonadotropins and (free) E2 levels were unchanged, serum E2/T ratio decreased (p < 0.0125). Total amount of urinary T increased non-significantly with mean increases of 53 % one year after GBS (p = 0.026). Urinary E2/T, estrone/T, 3α-androstanediol/T and androsterone/T ratios decreased after GBS (p < 0.0125). Restoration of circulating T levels during weight loss in this population is not only brought about by normalization of circulating SHBG levels, but increased production of and alterations in T metabolism also contribute. More specifically, relative decreases in aromatization and lower 5α-reductase activity might also be involved in restoring T levels in men with obesity.